Preliminary support for using the Atypicality Scale from the Behavior Assessment System for Children, Second Edition, to screen for psychosis‐spectrum disorders within a college counselling centre. Issue 2 (21st May 2020) - Thompson, Elizabeth C.; DeLuca, Joseph S.; Petti, Emily; Rakhshan Rouhakhtar, Pamela; Schiffman, Jason
Abstract: Aim: Evidence supports the use of brief psychosis‐spectrum screeners for identifying individuals at risk for psychosis. Screening has not been well‐studied in help‐seeking college samples. This study investigated the use of the Behavior Assessment System for Children, Second Edition (BASC‐2) Atypicality Scale as a psychosis‐spectrum screening tool within a university counselling centre. Methods: Atypicality scores from the BASC‐2 were compared to interview‐based assessment, the Structured Interview for Psychosis‐risk Syndromes (SIPS), to explore associations across the measures and evaluate the scale's ability to identify individuals who meet criteria for a psychosis‐spectrum diagnosis. Results: Forty‐three participants completed the BASC‐2 and SIPS, and 23 were SIPS‐positive. Compared to the SIPS‐negative group, the SIPS‐positive group had significantly higher Atypicality scores. Exploratory results indicated that Atypicality scores identified SIPS‐positive individuals with an overall accuracy of 72% (78% sensitivity, 65% specificity). Conclusion: The Atypicality Scale may be an appropriate first‐line psychosis‐spectrum screening tool in college counselling centres.